Temperature difference in close-spaced sublimation (CSS) growth of CdTe thin film on ultra-thin glass substrate - Doroody C.; Rahman K.S.; Abdullah S.F.; Harif M.N.; Rosly H.N.; Tiong S.K.; Amin N. (Elsevier B.V., 2023)
In this study, cadmium telluride (CdTe) thin films were grown for the first time ever on ultra-thin (100 m) Schott D263T glass substrates via high temperature deposition process namely close-spaced sublimation (CSS). CdTe thin films were deposited under different source and substrate temperatures ranging from 500 ? to 700 ? to investigate the influence of deposition temperature on the properties of CdTe thin films grown on ultra-thin Schott glass substrates. X-ray diffraction (XRD) analysis illustrated cubic CdTe structure with a sharp peak at (1 1 1) orientation. The scanning electron microscope (SEM) study elucidated that the grain growth and surface morphology were highly dependent on the deposition temperature. UVVis results showed approximate optical band gap range of 1.611.66 eV. Carrier concentration and resistivity were found in the order of 1013 cm?3 and 105 ?-cm, respectively. Structural and opto-electronic characteristics were optimized for the best temperature range to be used for CdTe film deposition in CSS growth. Optimum conditions for CdTe film growth on ultra-thin (100 m) substrate were found in the range of 500 ?600 ? for substrate and source temperature. 2020